ANALISA USAHA BUDIDAYA IKAN NILA MERAH (Oreochromis niloticus) SECARA TERPADU DENGAN AYAM (LONG-YAM) DI KABUPATEN BENGKULU UTARA - Ta'aladin, Zamdial (Jurnal AGRISEP, 2012)
The objectives of this research were to know the feasibility of effort of Nila merah (Oreochromis niloticus) culture in integrated manner with chicken (Long-Yam). This research was conducted in Bengkulu Utara Regency, Bengkulu Province. The data were analyzed by financial-economic aspect using Net Benefit-Cost Ratio (Net B/C Ratio), NPV (Net Present Value) and IRR (Internal Rate of Return). The result of financialeconomic aspect analysis were obtained Net B/C Ratio = 1.71, NPV = 5,103,169 and IRR = 33,00. Based on the result of this analysis showed that the effort unit of nila merah (Oreochromis niloticus) culture in a integrated manner with chicken is feasible and can developed in Bengkulu Utara Regency.